Head Teachers’ Ideologies Behind English Medium Instruction in the Community Schools - Bhatta, Tek Raj (Journal of NELTA, 2023)
English, a global lingua franca, is neither a second nor an offi cial language in Nepal. However, several community schools existing in Nepal have implemented English Medium Instruction (EMI, hereafter). Therefore, this study examines the ideologies of community schools’ head teachers behind starting EMI. In addition to this, it aims to discover implementational challenges during the initial days of EMI adoption. I have adopted narrative inquiry approach of qualitative research to bring out the ideologies of the head teachers behind starting EMI in community schools in Dhangadhi. I purposively selected three head teachers and conducted semi-structured interviews with them to elicit stories. Interpretation of the stories revealed various ideologies of head teachers behind starting EMI in community schools. The study concludes that EMI in community schools is adopted to assist them in enrolling and increasing the number of students. Moreover, it has challenged the stereotyping of the public towards community schools. Likewise, the study reveals several legal challenges, like the admission of preschool-aged children to primary schools and tuition fees charged to the students, which is against the Constitution of Nepal 2015 faced by community schools in the initial days of EMI adoption. The study’s findings present the adoption of EMI in community schools in the form of neoprivatisation. Finally, the study provides insights to stakeholders willing to initiate EMI community schools in Nepal.